Ekstrakurikuler Berbasis Nilai Pendidikan Agama Islam Implementasi Profil Pelajar Pancasila di Sekolah Menengah Pertama Negeri 16 Pekanbaru - Mila Mahmudah; Daisy Jhonny Pilly; Joko Purnomo; Zakaria (Jurnal Keislaman)
This research focuses on extracurricular activities at State Middle School 16 Pekanbaru which focuses on meeting the needs of students by implementing the independent curriculum to prepare students for the changing lives of the 21st century which contains the characteristics and local potential of State Middle School 16 Pekanbaru which results in students having a Pancasila Student Profile which has six dimensions, namely faith and devotion to God Almighty and noble character, working together, reasoning critically, creatively, independently, and global diversity. and one of the focuses is value-based Islamic Religious Education. This research discusses the activities carried out at Pekan Baru 16 State Junior High School which aim to improve the spiritual quality of students. This research was conducted using a qualitative method approach. Through in-depth interview techniques, observation, and documentation, data was collected from informants which was then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the research show an increase in students' ability to carry out their obligations as Muslims so that they are expected to be able to create noble morals in accordance with the goals of the Pancasila Student profile.